Intussusceptive Lymphangiogenesis in Lymphatic Malformations/Lymphangiomas. Issue 11 (8th July 2019) - Díaz‐Flores, Lucio; Gutiérrez, Ricardo; García, Maria D. P.; Carrasco, José L.; Sáez, Francisco J.; Díaz‐Flores, Lucio; González‐Gómez, Miriam; Madrid, Juan F.
ABSTRACT: Intussusception in lymphatic vessels has received less attention than in blood vessels. In tumors and pseudotumors of blood vessels with intravascular papillary structures, including sinusoidal hemangioma and intravascular papillary endothelial hyperplasia, we observed exuberant intussusceptive angiogenesis, as well as the similarity between papillae (term used by pathologists) and pillars/folds (hallmarks of intussusceptive angiogenesis). A similar response could be expected in lymphangiomas (lymphatic malformations and reactive processes rather than tumors) with papillae. The aim of this work is to assess whether papillae/pillars/folds and associated structures (vessel loops and septa) are present in lymphangiomas, and to establish the characteristics and formation of these structures. For this purpose, we selected lymphangiomas with intraluminal papillae (n = 18), including cystic, cavernous, circumscriptum, and progressive types, of which two cases of each type with a greater number of papillae were used for serial histologic sections and immunohistochemistry. The studies showed a) dilated lymphatic spaces giving rise to lymphatic–lymphatic vascular loops, which dissected and encircled perilymphatic structures (interstitial tissue structures/ITSs and pillars/posts), b) ITSs and pillars, surrounded by anti‐podoplanin‐positive endothelial cells, protruding into the lymphatic spaces (papillary aspect), and c) splitting, remodeling, linear arrangement, and fusion of papillae/pillars/folds, forming papillary networks and septa. In conclusion, as occurs in blood vessel diseases, the development of lymphatic vessel loops, papillae/pillars/folds, and septa (segmentation) supports intussusceptive lymphangiogenesis and suggests a piecemeal form of intussusception. This intussusceptive lymphangiogenesis in lymphatic diseases can provide a basis for further studies of lymphatic intussusception in other conditions, with clinical and therapeutic implications. Anat Rec, 302:2003–2013, 2019. © 2019 American Association for Anatomy